The role of chloramine species in NDMA formation. (1st September 2018) - Selbes, Meric; Beita-Sandí, Wilson; Kim, Daekyun; Karanfil, Tanju
Abstract: N -nitrosodimethylamine (NDMA), a probable human carcinogen disinfection by-product, has been detected in chloraminated drinking water systems. Understanding its formation over time is important to control NDMA levels in distribution systems. The main objectives of this study were to investigate the role of chloramine species (i.e., monochloramine and dichloramine); and the factors such as pH, sulfate, and natural organic matter (NOM) influencing the formation of NDMA. Five NDMA precursors (i.e., dimethylamine (DMA), trimethylamine (TMA), N, N -dimethylisopropylamine (DMiPA), N, N- dimethylbenzylamine (DMBzA), and ranitidine (RNTD)) were carefully selected based on their chemical structures and exposed to varying ratios of monochloramine and dichloramine. All amine precursors reacted relatively fast to form NDMA and reached their maximum NDMA yields within 24 h in the presence of excess levels of chloramines (both mono– and dichloramine) or excess levels of dichloramine conditions (with limited monochloramine). When the formation of dichloramine was suppressed (i.e., only monochloramine existed in the system) over the 5 day contact time, NDMA formation from DMA, TMA, and DMiPA was drastically reduced (∼0%). Under monochloramine abundant conditions, however, DMBzA and RNTD showed 40% and 90% NDMA conversions at the end of 5 day contact time, respectively, with slow formation rates, indicating that while these amine precursors react preferentially with dichloramine to form NDMA, they can also react with monochloramine in the absence of dichloramine. NOM and pH influenced dichloramine levels that affected NDMA yields. NOM had an adverse effect on NDMA formation as it created a competition with NDMA precursors for dichloramine. Sulfate did not increase the NDMA formation from the two selected NDMA precursors. pH played a key role as it influenced both chloramine speciation and protonation state of amine precursors and the highest NDMA formation was observed at the pH range where dichloramine and deprotonated amines coexisted. In selected natural water and wastewater samples, dichloramine led to the formation of more NDMA than monochloramine. Graphical abstract: Image 1 Highlights: Most NDMA precursors react mainly with dichloramine to form NDMA. Some precursors react with both mono- and dichloramine to form NDMA at different rates. NDMA formation was faster and higher as dichloramine concentration increases. NOM decreased NDMA formation due to competition or binding with amine precursors. NDMA formation in natural water samples was mostly limited by the availability of dichloramine.